Inflammatory markers partially mediate the association between volatile organic compounds exposure and hyperlipidemia: a nationally representative cross-sectional study from NHANES - Nie, Yaxiong; He, Zining; Liu, Bei; Li, Jiaai; Liu, Yanyu; Su, Xin; Yan, Zhiqiang; Li, Zheng; Yan, Chang; Lu, Qian; Fu, Yanfang; Yang, Wanyu; et al. (Frontiers in Public Health, 2025)
BackgroundWhile studies have explored associations between volatile organic compounds (VOCs) and metabolic diseases, evidence specifically linking VOCs to hyperlipidemia remains limited. This study aimed to examine the association between urinary VOC metabolites and hyperlipidemia prevalence in U.S. adults.MethodsLeveraging data from the 2011–2018 National Health and Nutrition Examination Survey (NHANES), this study employed weighted logistic regression, restricted cubic spline (RCS) models, weighted quantile sum (WQS) regression, quantile-based g-computation (qgcomp), and Bayesian kernel machine regression (BKMR) to evaluate associations of individual and mixed VOC exposures with hyperlipidemia. All models were adjusted for covariates including sex, age, race/ethnicity, poverty income ratio (PIR), education level, marital status, body mass index (BMI), smoking status, alcohol consumption, and urinary creatinine. Subgroup analyses assessed effect modifications by sex and age. Multiple-mediator analysis examined the roles of inflammatory biomarkers (white blood cell, lymphocyte, and neutrophil counts) in the association between VOC exposure and hyperlipidemia.ResultsAmong 1,979 included participants, weighted logistic regression identified 13 VOC metabolites significantly associated with increased hyperlipidemia risk. Subgroup analyses revealed stronger effects in females and individuals aged <60 years. The RCS model demonstrated positive linear dose–response relationships for hyperlipidemia risk with exposure to xylene, N, N-dimethylformamide, acrylonitrile, crotonaldehyde, 1,3-butadiene, and styrene. Mixture analyses showed significant positive associations via both WQS (1.312 [1.073, 1.606]) and qgcomp (1.296 [1.035, 1.623]), with N, N-dimethylformamide being primary contributor. However, BKMR detected no significant association. Multiple-mediator analysis indicated that inflammatory markers partially mediated the association between the VOC mixture and hyperlipidemia, and WBC was the leading mediator, accounting for 15.094% of the mediated effect.ConclusionThis study demonstrated significant positive associations of both individual and mixed VOC exposures with hyperlipidemia, with differential susceptibility observed in females and individuals aged <60 years. N, N-dimethylformamide contributed most to the association, and this effect was partly mediated by inflammatory biomarkers.